The Role of Teachers in Shaping Students’ Islamic Character in Islamic Senior High Schools - Aldianto, Reno; Pasaleron, Roni; Fitri, Rika (LP2M STAI Balaiselasa YPPTI Pesisir Selatan Sumatera Barat, 2025)
The formation of Islamic character in students is one of the main objectives that is not only oriented towards academic achievement, but also towards strengthening spiritual and moral values. Akidah Akhlak teachers play a central role in this process, because the subjects they teach are directly related to the foundations of faith, piety, and ethics in everyday life. This article aims to examine in depth how Akidah Akhlak teachers carry out this role, as well as the extent of their contribution in shaping the character of students who are faithful, pious, responsible, and able to maintain trust in life. This type of research is qualitative research using descriptive methods. This research method will obtain descriptive data in the form of spoken or written words. The data collected comes from interview transcripts, field notes, personal documents, and so on. The research informants in this study are Akidah Akhlak teachers, school principals, and students. The research instruments in this study are observation, interviews, and documentation. This study uses data analysis techniques, namely data reduction, data presentation, data verification or conclusion, and data credibility testing. This study also uses data validity assurance techniques. The results of this study are as follows: first, the role of Akidah Akhlak teachers in shaping students' faith and piety is to set a good example or model behavior and speech. Second, the role of Akidah Akhlak teachers in shaping students' sense of responsibility is to carry out activities in the classroom through learning materials that shape students' awareness of values. This can be improved through a process of education and learning in the classroom. Third, the role of Akidah Akhlak teachers as guardians of trust is to be honest in their duties in the Akidah Akhlak subject. The activities carried out are for students to complete assignments at school through Student Worksheets provided by Akidah Akhlak teachers.